M1 and M2 macrophages markers are alternately expressed during periapical lesion development - Carolina Maschietto PUCINELLI; Paulo NELSON-FILHO; Marília Pacífico LUCISANO; Jorge Esquiche LEÓN; Lúcia Helena FACCIOLI; Carlos Arterio SORGI; Clara Marina Pereira Cavalcanti SILVA; Lea Assed Bezerra da SILVA; Raquel Assed Bezerra da SILVA (Journal of Applied Oral Science)
Abstract Background This study evaluated the altered expression levels of genes and cytokines associated with M1 and M2 macrophages during the development of periapical lesion (PL). Methodology PL was induced in the lower first molars of 96 mice. After the experimental periods of two, seven, 14, 21, and 42 days, the animals were euthanized and their jaws were dissected and submitted to the following analyses: microscopic descriptive analysis and fluorescence microscopy morphometry of PL size (mm2); quantitative gene expression analysis by qRT-PCR for M1 (Cxcl10, Cxcl9, and Nos2) and M2 phenotypes (Arg1, Fizz1, Ym1, and Mrc1); and M1- (GM-CSF, IFN-γ, IL-6, IL-1β, TNF-α) and M2- (IL-4, IL-13, and IL- 10) related cytokines quantification by Luminex. Data were statistically compared by ANOVA, Tukey post-test, Kruskal-Wallis, and Dunn post-test (α=5%). Results PL area and inflammatory infiltrate increased over experimental periods. From a contextual view, a pro-inflammatory profile and a higher activation of M1 phenotype markers in the initial periods of two and seven days could be observed. On day 21, microscopic features and M2 subtype predominance indicated a repair attempt. However, on day 42, an acute exacerbation of immunoinflammatory process and return to the M1 macrophage profile were evidenced. Conclusion M1 and M2 macrophage polarization-related markers were expressed alternately throughout the experimental periods, according to the stage of PL progression.